Second Mesiobuccal Canal Evaluation Features with Cone-Beam Computed Tomography - Oleg Mordanov; Zurab Khabadze; Fatima Daurova; Inna Bagdasarova; Andrei Zoryan; Alena Kulikova; Anastasiya Blokhina; Rita Mustafaeva; Yusup Bakaev; Saida Abdulkerimova (International Journal of Dentistry)
Aim. The aim of the study is to evaluate the difference in MB2 prevalence with different slice thicknesses in maxillary first molars. Materials and Methods. Two hundred nonfilled MB2 canals in maxillary first molars of 156 people (75 females and 81 males) aged from 20 to 73 years old were evaluated with CBCT with different slice thicknesses: 0.5 mm, 1 mm, 3 mm, and 10 mm. A general analysis was performed out, as well as in the age groups and on gender groups. Results. Visualization with 0.5 mm and 1 mm slice thicknesses was 100% and generally equal, in both the male and the female group. General MB2 visualization with 3 mm slice thickness was 42% and 29% for the male group and 27% for the female group. No canals were visualized with 10 mm slice thickness. The study did not demonstrate a statistical difference in the MB2 prevalence between gender and age groups with the 3 mm slice thickness. Conclusion. The most valuable way to evaluate the root canal system in first maxillary molars with CBCT is using 1 mm slice thickness for both genders and every age group.